The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/trtr.1922
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Bilingualism to the Center of Guided Reading Instruction

Abstract: Coming this October! ILA Next introduces a new model for high-quality professional development in an online setting. This four-week event combines live and on-demand content that is timely, relevant, and responsive to the needs of today's literacy professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…To depart from a complex notion of equity for reading reform, educators need to be open to understanding how the fullness of students' individual and collective identities may demand an approach that looks differently across classroom contexts (Ascenzi-Moreno & Quiñones, 2020).…”
Section: A Time Of Opportunity: Understanding the Complexity Of Readi...mentioning
confidence: 99%
“…To depart from a complex notion of equity for reading reform, educators need to be open to understanding how the fullness of students' individual and collective identities may demand an approach that looks differently across classroom contexts (Ascenzi-Moreno & Quiñones, 2020).…”
Section: A Time Of Opportunity: Understanding the Complexity Of Readi...mentioning
confidence: 99%
“…Although scholarship focused on small‐group reading instruction sometimes recommends that teachers consider texts' purposes for content and literacy instruction (e.g., Conradi Smith et al., 2022; Fountas & Pinnell, 2012), there seems to be little focus on CSP and its integration into reading groups (for exception see Ascenzi‐Moreno & Quiñones, 2020). Research demonstrates that children's reading comprehension improves when they draw upon their cultural and linguistic knowledge (e.g., Cho & Christ, 2022) and when texts are relevant to them culturally (e.g., Clark, 2017).…”
Section: Differentiated Reading Groups and Culturally Sustaining Peda...mentioning
confidence: 99%
“…One study found that even proficient bilingual readers struggled to use punctuation appropriately in both English and Spanish, often misunderstanding the text as a result (Briceño, 2021). Teachers should make cross‐language connections transparent; in fact, when bilingual readers received explicit instruction on how word‐solving strategies in one language could be applied to another, they improved in their ability to decode (Ascenzi‐Moreno & Quiñones, 2020).…”
Section: Figurementioning
confidence: 99%